Diversity and potential of coffee plant types in Lawang Taji, Gunung Karang, Pandeglang Regency, Banten - lulu Lutfiah; Eni Nuraeni; Azizah Fauziah Rahma; Bima Oktavianto; Pepi Nur Susilawati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2024)
The challenge of cultivating coffee plants is that the process is still traditional, and the types of coffee that are superior are still limited. Therefore, data collection is needed to determine the potential of coffee plants in developing cultivation. The purpose of this research was to study the diversity and potential of coffee types and the ecological conditions of Gunung Karang coffee valley. The research was conducted from March to June 2024 at Lembur Kopi Citaman Lawang Taji, Sanim Village, Juhut Village, Karang Tanjung District, Pandeglang Regency, Banten. The sampling technique was purposive sampling, and the data obtained from observations and interviews were analyzed using descriptive qualitative methods. The results showed that six types of coffee can be cultivated, namely Arabica, Robusta, Liberica, Excelsa, Purpurascen, and Robusta. Menhir coffee had unique flavors and aromas with distinctive flavors of brown sugar, nuts, chocolate, spices, vanilla, and acid. Morphological analysis of the six types of coffee showed the same characteristics in the branching system. The ecological characteristics of coffee plants included altitude criteria of 550-600 masl, pH between 5-8, air temperature 28-29 °C, air humidity between 70%-76%, and humus-dominant soil conditions. These land criteria were categorized as sufficient to meet coffee growth. Keywords: coffee farm; coffee ecology; coffee menhir; morphology of coffee